The Gendered Effects of a Graduated Sanctions Model on Probation Outcomes in Kansas - Browne, George E. (Criminal justice policy review, 2022)
Although originally perceived as an evidence-based program, there has been a continual debate on the true effectiveness of the graduated sanctions model for probation. Nonetheless, what is missing in the literature is an examination of how this program may affect women under supervision differently than men. Utilizing probation violation hearing data from the Kansas Sentencing Commission (KSSC), this study examines the impact of Kansas’ 2013 House Bill 2170 (HB 2170) on probation outcomes across gender. Results indicate that the use of graduated sanctions scheme through HB 2170 is associated with a higher likelihood of receiving an imprisonment disposition for women probation technical violators than men. Major findings and policy implications will be discussed.